Priorities and expectations of researchers, funders, patients and the public regarding the funding of medical research: results from the PERSPECT qualitative study - Mayank Goyal; Aravind Ganesh; Tanaporn Jaroenngarmsamer; Bogna A Drozdowska; Joachim Fladt; Arshia Sehgal; Nora Cristall; Rosalie Victoria McDonough (BMJ Open)
Background Ideally, medical research provides crucial data about disease processes, diagnoses, prognoses, treatment targets and outcomes, and systems of care. However, medical research is costly, and funding is difficult to receive because the processes are highly competitive. There is a paucity of data on the perspectives of researchers, funders, patients and the public about current funding paradigms. This study sought to understand the priorities and opinions of each group to better guide meaningful innovation in research funding processes.Method In this Priorities & Expectations of Researchers, Funders, Patients and the Public Regarding the Funding & Conduct of Stroke Research study, we conducted in-depth interviews with medical researchers, funders, patients and members of the general public to learn their opinions of the current funding process and thoughts about alternative approaches. We used both purposive and snowball sampling to recruit participants and conducted semistructured interviews. The study ended when thematic saturation was attained. Qualitative analysis followed inductive grounded theory methodology.Results 41 interviews were completed (11 researchers, 10 funders, 10 patients, 10 members of the general public; 61% female). Interviewees expressed a high interest in supporting a comprehensive evaluation of the research grant funding process while integrating funding mechanisms that are more inclusive and reduce bias in topic selection and researchers who receive funds. Participants acknowledged a gap in patient and public involvement in setting a research agenda, choosing topics to be studied and focusing on specific outcomes. Crowdfunding was identified as an alternative strategy that could facilitate research democratisation; however, participants emphasised the importance of expert review of research proposals, as in current processes to continue to support rigour and trust in research proposal quality.Conclusion Our research revealed stakeholder concerns about the transparency and equity of current research funding paradigms. Suggestions to democratize research and explore alternative fundraising platforms necessitate a fundamental shift in traditional research funding processes.